Qualidade de vida relacionada à saude de adolescentes com doenças crônicas - Rezio, Marília Arantes (2015)
Objective: to evaluate the health related quality of life (HRQOL) in adolescents, at the same time, across four different chronic conditions; to compare HRQOL with these chronic conditions to healthy adolescents; to examine convergence in self- reported and parent-proxy reported patient HRQOL across these conditions; and to identity demographic, socioeconomic and health-status variables associated with impairment in HRQOL. Study design: Cross-sectional study with 276 adolescents with cancer, type 1 diabetes mellitus, overweight, asthma and without medical diagnosis of diseases (control group) assisted by public health service. Adolescents and caregivers completed age-appropriate self-report and/or parent- proxy report generic HRQOL measures using the Varni PedsQL™. Results: Participants were 50.7% male and had a mean age of 14±2 years. Adolescents with cancer had lower overall HRQOL as well as poorer all dimensions than healthy participants and other chronic conditions. Caregivers reported similar HRQOL by proxy-report than adolescents self-reported across chronic diseases, and in control group, reported better scores in all dimensions. Maternal education, family income and marital status of parents were correlated with the dimensions of HRQOL. The probability of cancer has HRQOL affected was higher when compared to other chronic disease. Conclusion: Adolescents with cancer, overweight e asthma, in comparison to healthy adolescents, reported poorer overall HRQOL as well as poorer scholar dimension. Cancer was the most chronic disease that has the dimensions of HRQOL affected. The results could subsidize health professionals, institutions, schools and governments to biopsychosocial attention and early interventions.